Return versus Onward Migration: Go Back or Move On? - Govert Bijwaard; Jackline Wahba (Institute of Labor Economics (IZA), 2022)
This paper examines the impact of unemployment on out-migration by distinguishing between return and onward migration and controlling for total earnings. We use Timing-of-Events models and control for the endogeneity of total earnings, unemployment and out-migration using administrative data from the Netherlands. Our findings suggest that unemployment triggers return migration more than onward migration. When total earnings are low unemployment increases the hazard of return migration. When total earnings are high the hazard rate of onward migration for unemployed immigrants increases. Thus, these findings highlight that out-migration is affected both by unemployment and by total earnings as well as by the interaction between the two.
Keywords: F22; J61; C41; 330; migration dynamics; temporary migration; target savers; unemployment